Sand layered molding machine and sand layered molding method
The sand additive manufacturing machine and method use controlled laser power and resin-coated sand to achieve precise and cost-effective molding of complex shapes by minimizing heat transmission and ensuring adequate strength.
Patent Information
- Application Number
- JP2023195693
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-11-17
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2038-10-11
AI Technical Summary
Existing sand additive manufacturing technologies using high-output laser light are costly and can compromise the shape and dimensional accuracy of the final product due to heat transmission to adjacent layers, making them unsuitable for complex and precise mold creation.
A sand additive manufacturing machine and method utilizing resin-coated sand with a resin ortho ratio of 55% to 75% and a laser output of 10W to 80W, combined with controlled scanning and layer formation, to achieve precise molding with reduced costs and improved accuracy.
The method ensures high molding accuracy while keeping costs low by using low-power laser beams that minimize heat transmission, allowing for the creation of complex shapes with sufficient strength for the final product.
Smart Images

Figure 0007619578000003 
Figure 0007619578000004 
Figure 0007619578000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a sand layered manufacturing machine and a sand layered manufacturing method that irradiates a layer of resin-coated sand with laser light that hardens the resin. [Background technology]
[0002] A casting mold consists of a main mold and a core. The main mold is made of a sand mold or metal mold, but the core is generally made of a sand mold that maintains its strength with an organic binder. The core is used to form the hollow part of the casting, and after casting, the core that formed the hollow part can be easily separated from the casting because the binder burns. In particular, for products with complex shapes or narrow grooves, the "shell molding method" is often used, in which "coated sand" is made by coating sand with phenolic resin, a thermosetting resin, as a binder, and then blowing it into a heated mold to form the product. In addition, when a core forms a narrow hole shape inside the casting, gas defects occur due to the gas pressure generated by the resin, and it is known that a countermeasure to this problem is to make the core hollow, which ensures breathability of the core and allows the gas to be discharged, thereby avoiding gas defects. On the other hand, non-thermosetting binders are solidified by adding a curing agent or through a gas curing reaction, so they can be molded at room temperature, can be molded without using a metal mold, and do not require a heated metal mold. However, since they cannot be molded into hollow shapes, gas escape is insufficient and gas defects are likely to occur.
[0003] The shell molding method has the advantage that the unhardened part inside the core can be discharged (reversed sand flushing) by inverting the mold when the surface layer is thermally hardened after blowing into the mold, thereby forming a hollow core. However, it requires a dedicated molding machine, not a general-purpose machine that is widely used, and there are limitations on the hollow shape when it is desired to provide small holes to more efficiently release the gas generated by the core during casting, and hollow parts in each part of the core, and sand can only be flushed from the blowing port, making it difficult to form a complex hollow shape. Furthermore, in the case of prototypes or non-mass-produced products, there are problems such as the difficulty of forming the core because the mold is expensive, and the financial difficulty of considering the shape of the core using multiple molds.
[0004] To solve these problems, it has been proposed in recent years to use additive manufacturing techniques to create molds (see, for example, Patent Document 1, etc.). In the additive manufacturing technique described in Patent Document 1, a layer of coated sand is formed and a hardener is selectively sprayed onto the layer, so that the portion where the hardener is sprayed becomes a hardened portion. Once the spraying of the hardener is complete, a new layer of coated sand is formed on the layer with the hardened portion, and the hardener is again selectively sprayed to provide a hardened portion in the new layer of coated sand. By repeating the layer formation and the selective spraying of the hardener, a three-dimensional mold with stacked hardened portions can be obtained.
[0005] However, in order to realize the additive manufacturing technology using a hardener described in Patent Document 1, a very large investment is required.
[0006] By the way, by using the additive manufacturing technology, it is possible to obtain various three-dimensional objects, not limited to casting molds. In addition to the additive manufacturing technology using the above-mentioned hardener, an additive manufacturing technology using laser light has also been developed (see, for example, Patent Document 2, etc.). In the additive manufacturing technology described in Patent Document 2, a layer of resin-coated sand is irradiated with laser light that hardens the resin, and the part of the layer of resin-coated sand that is irradiated with the laser light becomes a hardened part. When the irradiation of the laser light is completed, a new layer of resin-coated sand is formed on the layer with the hardened part, and the new layer of resin-coated sand is irradiated with laser light again to provide a hardened part in the new layer of resin-coated sand. Thereafter, the layer formation and the irradiation of the laser light are repeated to obtain a three-dimensional object with hardened parts stacked on top of each other. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2015 / 29935 [Patent Document 2] JP 2005-169434 A DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0008] However, the additive manufacturing technology using laser light described in Patent Document 2 irradiates high-power laser light of, for example, 5 kW, which inevitably increases the cost of the device. In addition, when high-power laser light is used, the heat of the laser light is transmitted to the outer region or lower region adjacent to the hardened part, and the shape and dimensional accuracy of the completed model may not be as designed.
[0009] In view of the above circumstances, an object of the present invention is to provide a sand additive manufacturing machine that is inexpensive yet has high molding accuracy, and a sand additive manufacturing method that has high molding accuracy while suppressing molding costs. [Means for solving the problem]
[0010] The sand layering machine that solves the above-mentioned objectives is as follows: A storage area for resin-coated sand, a layer forming means for forming a layer of the resin-coated sand stored in the storage section; an irradiation unit that irradiates the layer with laser light to harden the resin; the layer forming means forms a new layer of resin-coated sand on the layer when the irradiation of the laser light to the layer is completed; The storage unit stores resin-coated sand in which the surfaces of sand particles are coated with a resin having an ortho ratio of 55% or more and 75% or less, The irradiation unit irradiates laser light with an output of 10 W or more and 80 W or less, The output of the laser light irradiated by the irradiation unit is P [W], the scanning speed of the laser light is v [mm / s], the scanning pitch of the laser light is w [mm], and the layer pitch in the layer forming means is h [mm], where P / (vwh) [ws / mm 3 ]=E[J / mm 3 When the energy density E is expressed as 1.3 J / mm, the output of the laser beam is 10 W or more and 80 W or less, and the energy density E of the laser beam is 1.3 J / mm3 The present invention is characterized in that:
[0011] Also, The irradiation unit irradiates laser light with an output of 10 W or more and 30 W or less, When the output of the laser beam is between 10 W and 30 W, the energy density E of the laser beam is 1.3 J / mm 3 The above may be a feature.
[0012] Here, the layer may be stacked on a base, the base may be lowered at a predetermined pitch when the irradiation of the laser light to the layer is completed, and the layer forming means may form a new layer of resin-coated sand after the base is lowered at the predetermined pitch. In addition, the layer forming means may be provided with an elevating means for raising and lowering the base at a predetermined pitch. Alternatively, the layer may be stacked on a base placed in a frame, the frame may be raised at a predetermined pitch when the irradiation of the laser light to the layer is completed, and the layer forming means may form a new layer of resin-coated sand after the frame is raised at the predetermined pitch. In addition, the layer forming means may be provided with an elevating means for raising and lowering the frame at a predetermined pitch.
[0013] The layers may be stacked on a base, and the layer forming means may rise at a predetermined pitch when the irradiation of the laser light to the layer is completed, and after rising at the predetermined pitch, a new layer of resin-coated sand may be formed. Furthermore, the layer forming means may be provided with an elevating means for raising the layer forming means at the predetermined pitch.
[0014] The storage section may also be provided with a supplying means for supplying the resin-coated sand stored in the storage section onto the base, and the layer forming means may form the layer on the base while supplying the resin-coated sand stored in the storage section onto the base.
[0015] According to the sand layered molding machine, sand particles are used whose surfaces are covered with a resin (hereinafter referred to as high ortho resin) whose ortho ratio, which indicates the ratio of ortho bonds, is 55% or more and 75% or less. In the case of a general resin that emphasizes strength, extremely high strength can only be obtained by heating it to around 250°C. However, in the case of high ortho resin, hardening progresses while it is heated to about 150°C, and a certain degree of strength is ensured. The low cost of the device is realized by making the irradiation unit capable of outputting only laser light of 10 W or more and 80 W or less. Even with such a low output, as described above, high ortho resin hardens while it is heated to about 150°C, and a certain degree of strength is ensured, so that a three-dimensional model in which hardened parts that have been irradiated with laser light and hardened are layered has at least a strength sufficient to be taken out of the sand layered molding machine. Furthermore, by suppressing the output of the laser light to a low output, the heat of the laser light is reduced from being transmitted to the outer area or the lower area adjacent to the hardened part, and molding accuracy is improved.
[0016] The sand particles of the resin-coated sand stored in the storage unit may be ceramic artificial sand. That is, the ceramic artificial sand may be 100% by mass. The ceramic artificial sand has a lower thermal conductivity than commonly used silica sand, and the diffusion of the heat of the laser beam to the outer region or the lower region is further reduced, thereby further improving the molding accuracy.
[0017] In addition, in the sand layered manufacturing machine, The irradiation unit may be configured to irradiate the entire desired shape with the laser light by scanning, and then irradiate the laser light so as to trace the outline of the shape.
[0018] In addition, in the sand layered manufacturing machine, The output of the laser light when the irradiating unit irradiates the entire shape with the laser light may be the same as the output of the laser light when tracing the contour of the shape.
[0019] The irradiation unit may also be characterized in that it irradiates the laser light with a lower output power of the laser light when tracing the contour of the shape than the output power of the laser light when irradiating the entire shape with the laser light.
[0020] In addition, in the sand layered manufacturing machine, The irradiation unit may be characterized in that it irradiates the entire desired shape with laser light by scanning, and then irradiates the laser light so as to trace the outermost edge that is adjacent to and outside the contour of the shape.
[0021] In addition, in the sand layered manufacturing machine, The irradiation unit may be configured to irradiate laser light across multiple layers of stacked resin-coated sand to harden multiple support parts, which become thinner toward the top, at distributed positions, and then irradiate laser light across multiple layers of resin-coated sand stacked on top of the multiple support parts to harden the product parts connected to each of the multiple support parts.
[0022] The term "distributed" as used herein means that the product portion is supported at multiple points so as not to bend.
[0023] According to the above aspect, deformation of the product part is suppressed. In addition, when the product part is removed from the sand layer molding machine, the product part is easily broken at the boundary between the product part and the support part because the support part is tapered toward the upper part. This makes it easy to remove the product part.
[0024] If the support part is solid, the diameter of the upper end surface may be 2 mm or more and 7 mm or less. If it is less than 2 mm, it becomes difficult to support the product part, and the product part may be deformed. On the other hand, if the finished area of the product part after folding near the boundary between the product part and the support part (near the upper end surface) exceeds 7 mm, not only will it become too large and the work will become difficult, but the dimensional accuracy may be affected by the finishing work. Also, the support part may be hollow, and in this case, the thickness, which is the difference between the outer diameter and the inner diameter, is 0.5 mm or more and 3.5 mm or less, and the outer diameter of the upper end has a lower limit of 2 mm, the same as in the case of a solid part, but an upper limit of 20 mm, exceeding 7 mm.
[0025] In addition, in the sand layered manufacturing machine, The resin-coated sand stored in the storage unit is supplied to the storage unit, and the resin-coated sand is temporarily stored in a lump form in a storage unit. The layer forming means may be characterized in that it spreads the lump of resin-coated sand temporarily stored in the storage section into a layer to form the layer of resin-coated sand.
[0026] In this way, a layer of uniform thickness can be formed with a simple structure.
[0027] In addition, the apparatus may include a base on which the layers are stacked, and the storage section may be provided on the base or may be provided upstream of the base, and the layer forming means may be configured to spread lumps of resin-coated sand temporarily stored in the storage section onto the base.
[0028] The sand additive manufacturing method that solves the above object is as follows: A method for layering sand, comprising alternately repeating a step of forming a layer of resin-coated sand in which the surface of a sand particle is coated with a resin having an ortho ratio of 55% or more and 75% or less, and a step of irradiating the layer with a laser beam having an output of 10 W or more and 80 W or less to harden the resin, thereby forming a hardened layer, and stacking the hardened layers, the method comprising: a first step of forming a base plate by alternately repeating the layer formation and the laser light irradiation; A plurality of support parts which become thinner toward the top are formed at distributed locations on the base plate during the layer formation. a second step of alternately repeating the laser light irradiation and the second step of forming a shape; The method is characterized by having a third step of alternately repeating the layer formation and the laser light irradiation on the multiple support parts to form product parts connected to each of the multiple support parts. Effect of the Invention
[0029] The sand layered modeling machine of the present invention is inexpensive yet has high molding accuracy, and the sand layered modeling method of the present invention increases molding accuracy while suppressing modeling costs. [Brief description of the drawings]
[0030] [Figure 1] FIG. 1 is a cross-sectional view of a sand layered manufacturing machine according to an embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing a state in which laser light is irradiated in the sand layered manufacturing machine shown in FIG. 1. [Diagram 3] FIG. 1 is a schematic diagram showing a state in which laser light is irradiated onto resin-coated sand. [Figure 4] FIG. 13 is a diagram showing an example of the relationship between a cross-sectional pattern on a computer and an actual irradiation area. [Diagram 5] FIG. 13 is a diagram showing another example of the relationship between the cross-sectional pattern on the computer and the actual irradiation area. [Figure 6] FIG. 2 is a diagram showing an example of a model formed by the sand layer molding machine of the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] Hereinafter, an embodiment of the present invention will be described.
[0032] FIG. 1 is a cross-sectional view of a sand layered manufacturing machine according to one embodiment of the present invention.
[0033] The sand lamination molding machine 1 shown in FIG. 1 has a molding frame 10, a leveling member 20, and a supply device 30. The molding frame 10 is a rectangular frame member, and a stacking plate 11 and a lifting mechanism 12 are provided inside. The stacking plate 11 is raised and lowered by the lifting mechanism 12. The lifting mechanism 12 can set a value of a descent pitch, and the stacking plate 11 descends stepwise for each descent pitch set in the lifting mechanism 12. In this embodiment, the descent pitch can be set in the range of 0.1 mm to 0.7 mm, but it is preferable to set the length to a length greater than 1 time and less than 3 times the particle size of the resin-coated sand described later. In the initial state of the stacking plate 11, the height position of the surface 11a of the stacking plate 11 coincides with the height position of the upper edge 10t of the molding frame 10. Flange portions 101, 102 are provided on one end side (left side in FIG. 1) of the molding frame 10 and the other end side (right side in FIG. 1), respectively, and a supply device 30 is disposed above the flange portion 101 on the one end side.
[0034] The leveling member 20 is a blade that extends in the width direction of the molding frame 10 (a direction perpendicular to the paper surface in FIG. 1), and its initial position is a position above the flange portion 101 on one end side of the molding frame 10. The leveling member 20 moves from one end side where the supply device 30 is disposed to the other end side on the opposite side, with the position of the lower end 20b aligned with the height position of the upper edge 10t of the molding frame 10 (see the hollow arrow in FIG. 1(b)).
[0035] The supply device 30 stores the resin-coated sand rs and supplies a fixed amount of the resin-coated sand rs from a supply port 301 onto a flange portion 101 at one end of the molding frame 10. The supply port 301 is a slit-shaped opening extending in the width direction of the molding frame 10 (a direction perpendicular to the paper surface in FIG. 1), and a lump of the resin-coated sand rs is temporarily stored in the flange portion 101 at one end across the width direction of the molding frame 10. The supply device 30 corresponds to an example of a storage section, and the flange portion 101 at one end corresponds to an example of a storage section.
[0036] The resin-coated sand rs stored in the supply device 30 is made by coating the surface of ceramic-based artificial spherical sand with a resin having an ortho ratio of 55% or more and 75% or less.
[0037] The term "ceramic" as used herein refers to a material having a mullite crystal structure or a material having one or more of alumina, kaolin, silica, etc. as its main components. The artificial spherical sand is manufactured by a sintering method or a melting method, has high sphericity, and has a maximum peak in the particle size distribution in the range of 0.05 mm to 0.45 mm, and preferably in the range of 0.1 mm to 0.25 mm. The sphericity is determined based on the value calculated from the formula (perimeter of sand particle)2÷(4π×projected area of sand particle) as a value representing the degree of irregularity. If the value representing the degree of irregularity is 1, it is a perfect circle, and the larger the value, the greater the degree of irregularity. The artificial spherical sand has a value representing the degree of irregularity of 1.15 or less. If the value representing the degree of irregularity is 1.15 or less, the filling rate of the resin-coated sand rs is increased, the contact area between the resin-coated sand rs is increased, and the bonding force is strengthened. As for the sand, natural sand such as silica sand, zircon sand, chromite sand, etc. may be used, but since ceramic-based artificial sand has a lower thermal conductivity than natural sand, it is preferable to use only ceramic-based artificial sand in order to suppress unnecessary diffusion of the heat of the laser light. However, when the output of the laser light is set as low as possible, it is possible to prioritize efficient transmission of a small amount of heat energy by intentionally mixing in a large amount of natural sand with high thermal conductivity (e.g., silica sand) (e.g., 50% or more).
[0038] The resin in this embodiment is a high-ortho novolac type phenolic resin, which is a thermosetting resin represented by the following formula (1) in which phenol is bonded at the ortho position by methylene by reacting phenol with formaldehyde in an excess amount relative to formaldehyde and using a divalent metal salt as a catalyst.
[0039] [ka]
[0040] High ortho novolac type phenolic resin has a pH of 4 or more and 5 or less, an ortho ratio of 55% or more and 75% or less, many vacant para positions, and has properties such as rapid curing.
[0041] The stacking plate 11 shown in FIG. 1(a) is lowered by one level, and a stacking space sp (see FIG. 1(a)) corresponding to the thickness of the descending pitch is provided above the height position of the upper edge 10t of the molding frame 10. The resin-coated sand rs supplied onto the flange portion 101 is leveled by the leveling member 20 traveling toward the other end, and the stacking space sp is filled with the resin-coated sand rs from one end. That is, the leveling member 20 spreads the lump of resin-coated sand rs temporarily stored across the width of the molding frame 10 in the flange portion 101 on one end side into the stacking space sp in the form of layers, and a layer of resin-coated sand rs corresponding to the thickness of the descending pitch is formed in the stacking space sp. The leveling member 20 corresponds to an example of a layer forming means. In FIG. 1, a plurality of layers SL are formed on the surface 11a of the laminate plate 11, and in FIG. 1(b), the leveling member 20 has moved from one end side to the other end side on the plurality of layers SL to more than halfway, and a new layer is further formed. According to the sand layered molding machine 1 of this embodiment, a layer SL of uniform thickness can be formed with a simple structure. In addition, the supply port 301 may be worn by the resin-coated sand rs, and the opening area may become large. When the opening area becomes large, the amount of resin-coated sand rs temporarily stored in the flange portion 101 on the one end side increases. However, according to the sand layered molding machine 1 of this embodiment, the thickness of the layer SL is determined by the height position of the leveling member 20 that spreads the lump of resin-coated sand rs in layers, so that even if the amount of resin-coated sand rs temporarily stored increases, the thickness of the layer SL does not increase. Furthermore, even if the leveling member 20 is worn down by the resin-coated sand rs, replacing the leveling member 20 is much easier than replacing the supply device 30.
[0042] Fig. 2 is a cross-sectional view showing a state in which a laser beam is irradiated in the sand layering machine shown in Fig. 1. In Fig. 2, the layer SL, which was formed more than halfway as shown in Fig. 1(b), is formed over the entire surface of the inside of the molding frame 10 (the entire surface of the layering plate 11).
[0043] The sand layered molding machine 1 also has a laser oscillator 40, a scanner 50, and a control unit 60. The laser oscillator 40 emits a semiconductor laser beam, and the output value can be set in the range of 10 W to 80 W. If the output is less than 10 W, the thermal energy supplied by the laser beam is insufficient, the temperature of the resin-coated sand does not rise sufficiently, and thermal curing becomes difficult, so by limiting the output to 80 W, the device can be made low-priced. Furthermore, it is more preferable to use a laser oscillator whose output value can be set in the range of 25 W to 50 W. With an output value of 25 W or more, the modeling time is shortened and modeling efficiency is improved, and by limiting the output to 50 W, the device can be made even more inexpensive.
[0044] The scanner 50 includes a condenser lens 501 that condenses the laser light emitted by the laser oscillator 40, and a rotating mirror 502 that continuously changes the irradiation angle of the laser light. In Fig. 2, the laser light is indicated by a gray arrow line.
[0045] To form a desired three-dimensional structure using this sand layer modeling machine 1, first, the object to be formed is represented three-dimensionally on a computer, and data representing the cross-sectional pattern of each layer when the object is sliced in parallel into multiple layers at the above-mentioned descending pitch is created in advance. This data is then input to the control unit 60. Based on the input data, the control unit 60 causes the laser oscillator 40 to oscillate a laser beam and rotates the rotating mirror 502. That is, the control unit 60 controls the laser oscillator 40 and the rotating mirror 502 so that the laser beam is irradiated to a portion corresponding to the cross-sectional pattern and the laser beam is not irradiated to a portion not corresponding to the cross-sectional pattern.
[0046] In the area of each layer SL where the laser light is irradiated, the resin of the resin-coated sand rs is heated to about 150°C, melts, and undergoes a hardening reaction, and the adjacent artificial spherical sands of the resin-coated sand rs are bonded together by the hardened resin to form a hardened part. In Figures 1 and 2, the black parts of each layer SL are the hardened parts. In Figure 2, the hardened part is in the process of being formed in the top layer SL.
[0047] FIG. 3 is a schematic diagram showing the state in which the resin-coated sand is irradiated with a laser beam. In this example, the diameter of one particle of the resin-coated sand is such that the maximum peak of the particle size distribution is 0.1 mm, and in FIG. 3, all the particles of the resin-coated sand are shown with a diameter of 0.1 mm. The descent pitch is 0.2 mm. Therefore, the thickness of one layer of the resin-coated sand layer SL is 0.2 mm, which corresponds to two particles of the resin-coated sand, and one layer is configured in two rows, and three layers SL are shown in FIG. 3. Hereinafter, when distinguishing between these three layers, they will be referred to as the lower layer SL1, the middle layer SL2, and the upper layer SL3. In addition, in the uncured resin-coated sand RSP, the artificial spherical sand CS and the high-ortho-novolac type phenolic resin HOF covering its surface are shown separately. On the other hand, no distinction is made for hardened resin-coated sand, which is made by melting and hardening high-ortho-novolac phenolic resin HOF, and it is given the symbol RSH.
[0048] FIG. 3(a) is a schematic diagram showing a state in which a layer SL of resin-coated sand is irradiated with 5 kW laser light B5k.
[0049] The 5kW laser beam B5k has a high output, so it passes through the upper layer SL3 and reaches the middle layer SL2 below. Also, because the thermal energy supplied by the 5kW laser beam B5k is large, the cured resin-coated sand rsh is widely spread out. Furthermore, in FIG. 3(a), even a part of the uncured resin-coated sand that constitutes the middle layer SL2, which has been cured by the previous laser beam irradiation, has become the cured resin-coated sand rsh by the laser beam B5k irradiated to the upper layer SL3.
[0050] FIG. 3(b) is an example of this embodiment, and is a diagram that illustrates a state in which a layer SL of resin-coated sand rs is irradiated with 25 W laser light B25.
[0051] Since the output of the 25W laser beam B25 is relatively low, it stops within the upper layer SL3 and does not reach the middle layer SL2 below. That is, the laser beam B25 is irradiated up to the upper row constituting the upper layer SL3 shown in FIG. 3(b). More specifically, the upper row of resin-coated sand constituting the upper layer SL3 is irradiated up to about 5 / 6 from the top, not all of it. Also, since the thermal energy supplied from the 25W laser beam B25 is relatively small, the hardened resin-coated sand rsh does not spread as widely in the lateral direction as shown in FIG. 3(a), and also stays in the upper layer SL3 in the downward direction. That is, as described above, the laser beam B25 is irradiated only up to about 5 / 6 from the top of the resin-coated sand in the upper row constituting the upper layer SL3, but due to thermal conduction, the resin-coated sand rsh in the lower row constituting the upper layer SL3 has become hardened resin-coated sand rsh. Note that the resin-coated sand rsh in the middle layer SL2 has not become hardened resin-coated sand rsh. Therefore, in the example of this embodiment shown in FIG. 3(b), the shape and dimensional accuracy of the completed object are as designed, and high molding accuracy is guaranteed.
[0052] The hardened resin-coated sand rsh shown in Figure 3(b) is heated to approximately 150°C, causing it to melt and undergo a hardening reaction, resulting in a bending strength of approximately 300 N / cm2.
[0053] FIG. 4 is a diagram showing an example of the relationship between the cross-sectional pattern on the computer and the actual irradiation area.
[0054] In Fig. 4, the actual irradiation area is viewed from directly above, and the rectangle drawn by two-dot chain lines in the figure represents the outer edge (contour) of the cross-sectional pattern on the computer. As shown in Fig. 4(a), the rectangular cross-sectional pattern is made up of a left edge p1, a right edge p2, a front edge p3, and a rear edge p4. The X direction shown in Fig. 4(a) corresponds to the left-right direction in Figs. 1 and 2, and the Y direction corresponds to the width direction of the molding frame 10 (the direction perpendicular to the paper surface in Figs. 1 and 2).
[0055] In addition, the irradiated area is shown in black in Fig. 4. Here, the laser spot diameter in this embodiment is 0.1 mm in diameter, and the laser scanning pitch, which is the interval in the X direction relative to the Y direction scanning, is 0.15 mm. Therefore, the laser irradiated areas in the adjacent Y direction scanning lines do not overlap with each other, and a gap of 0.5 mm is generated, and strictly speaking, it is shown in white in Fig. 4, but it is omitted in the illustration and shown in black.
[0056] 4(b) shows a state a little while after the start of scanning, when five scans in the X direction have been completed and the sixth scan in the Y direction is in progress. In the first scan in the Y direction, the right edge p2 of the cross-sectional pattern on the computer is scanned from the front edge p3 to the back edge p4 of the cross-sectional pattern.
[0057] Fig. 4(c) is a diagram showing the state in which the final scanning in the Y direction is in progress after all scanning in the X direction is completed, and Fig. 4(d) is a diagram showing the state in which the final scanning in the Y direction is completed. In the final scanning in the Y direction, the left edge p1 of the cross-sectional pattern on the computer is scanned from the front edge p3 of the cross-sectional pattern to the back edge p4 of the cross-sectional pattern. As shown in Fig. 4(d), in this example, the laser light is irradiated over the entire area of the cross-sectional pattern on the computer.
[0058] Then, the laser light is irradiated again to the outer periphery (contour) of the cross-sectional pattern on the computer. That is, the laser light is irradiated so as to trace the contour of the cross-sectional pattern. In FIG. 4(e) and FIG. 4(f), the laser light irradiated to the outer periphery (p1 to p4) of the cross-sectional pattern is shown in grey. The example shown in FIG. 4(e) is an example in which the output of the laser light irradiated again to the outer periphery of the cross-sectional pattern is set to the same output (e.g., 50 W) as the output of the laser light when the entire cross-sectional pattern is irradiated. In the example shown in FIG. 4(e), the outer surface of the molded object is more firmly bonded and the surface stability is improved compared to the example shown in FIG. 4(d). On the other hand, the example shown in FIG. 4(f) is an example in which the output of the laser light irradiated again to the outer periphery of the cross-sectional pattern is reduced to a weaker output (e.g., 30 W) than the output of the laser light when the entire cross-sectional pattern is irradiated. The gray lines showing the irradiated laser beam are thinner if the output of the laser beam is weak, and the gray lines in FIG. 4(f) are thinner than those in FIG. 4(e). In the example shown in FIG. 4(f), the surface stability may be slightly inferior to that in FIG. 4(e), but the molding accuracy is maintained at a high level. That is, in the example shown in FIG. 4(e), if the thermal energy from the previous irradiation remains in the resin-coated sand, the same amount of thermal energy as the previous irradiation is added by re-irradiation, and the area of the hardened resin-coated sand may expand compared to the state shown in FIG. 4(d). In contrast, in the example shown in FIG. 4(f), the addition of thermal energy by re-irradiation is suppressed by lowering the output of the laser beam, and it is expected that both the surface stability and the molding accuracy can be balanced at a high level.
[0059] 5 is a diagram showing another example of the relationship between the cross-sectional pattern on the computer and the actual irradiation area. The following mainly describes the differences from the example shown in FIG.
[0060] In this figure 5, as in Figure 4, the actual irradiation area is viewed from directly above, and the two-dot chain rectangle in the figure represents the outer edge (contour) of the cross-sectional pattern on the computer. In Figure 5, the irradiated area is also shown in black. In Figure 5, as in Figure 4, the area between the irradiation areas on the scanning lines in the Y direction is strictly represented in white, but is omitted from the illustration and represented in black.
[0061] Fig. 5(a) is a diagram showing a state of the sixth Y-direction scan after five X-direction scans have been completed, similar to Fig. 4(a), at a stage a little time has passed since the start of scanning, similar to Fig. 4(a). In the example shown in Fig. 5(a), the first Y-direction scan scans in the Y direction from a position spaced one scan inward in the X direction from the right edge p2 of the cross-sectional pattern on the computer, from a position spaced the laser spot diameter inward in the Y direction from the front edge p3 of the cross-sectional pattern, to a position spaced the same laser spot diameter inward in the Y direction from the rear edge p4 of the cross-sectional pattern.
[0062] FIG. 5(b) is a diagram showing the state in which the final Y-direction scan is being performed after all the scanning in the X-direction is completed, with one scan spaced inward in the X-direction from the left edge p1 of the cross-sectional pattern on the computer, and FIG. 5(c) is a diagram showing the state in which the final Y-direction scan is completed. In the final Y-direction scan, scanning is performed in the Y-direction from the left edge p1 of the cross-sectional pattern on the computer, with one scan spaced inward in the X-direction from the position spaced by the laser spot diameter from the front edge p3 of the cross-sectional pattern to the position spaced by the laser spot diameter from the rear edge p4 of the cross-sectional pattern inward in the Y-direction. As shown in FIG. 5(c), in this example, the laser light is irradiated to an area one size smaller than the cross-sectional pattern on the computer. That is, after this, as shown in FIG. 5(d), in order to scan one revolution around the outer periphery of the cross-sectional pattern on the computer, the laser light is irradiated over the entire inner area with one revolution spaced. In FIG. 5(d), the laser light is irradiated to the outer periphery (contour) of the cross-sectional pattern on the computer. That is, the laser light is irradiated so as to trace the contour of the cross-sectional pattern. In other words, after irradiating the entire desired shape (here, the entire rectangular area one size smaller than the cross-sectional pattern on the computer) with the laser light, the laser light is irradiated so as to trace the outermost edge (here, the outer edge of the cross-sectional pattern) that is in contact with the contour of the shape and is outside the contour. In FIG. 5(d), the laser light irradiated to the outer edge (p1 to p4) of the cross-sectional pattern is also shown in gray. The example shown in FIG. 5(d) is an example in which the output of the laser light irradiated to the outer edge of the cross-sectional pattern is the same as the output of the laser light when an area one size smaller than the cross-sectional pattern is irradiated (for example, 50 W). However, by making the size of the area smaller than the cross-sectional pattern slightly larger, the output of the laser light irradiated to the outer edge of the cross-sectional pattern can also be set low (for example, 30 W). The example shown in FIG. 5 described above is an example in which laser light is irradiated onto an area smaller than the cross-sectional pattern on the computer by repeating scanning in the Y direction along the X direction, and then laser light is irradiated onto the outermost edge that is in contact with and outside the contour of that area, thereby irradiating laser light onto the entire area of the cross-sectional pattern on the computer.
[0063] FIG. 6 is a diagram showing an example of a model formed by the sand layered manufacturing machine of this embodiment.
[0064] The object shown in Fig. 6 is a hollow core C supported by a plurality of supporting parts F erected from a base plate B. Figs. 1 and 2 show the state in the middle of forming the object shown in Fig. 6. The hollow core C corresponds to the product part. The base plate B is molded on the surface 11a of the laminated plate 11, and has an area larger than the projected area of the hollow core C. The supporting parts F are distributed on the base plate B, becoming thinner toward the top, and the upper end surface is connected to the hollow core C. In other words, the supporting parts F connect the base plate B and the hollow core C. The base plate B is prevented from warping due to its area and thickness, and the supporting parts F support the hollow core C at a plurality of points to prevent the hollow core C from warping or distorting. According to the sand additive manufacturing machine 1 of this embodiment, multiple support parts F are hardened at distributed positions, and then laser light is irradiated across multiple layers of resin-coated sand SL stacked on top of the multiple support parts F, thereby hardening the hollow cores C connected to each of the multiple support parts F.
[0065] When the hollow core C is removed from the sand additive manufacturing machine 1, the support portion F becomes thinner toward the top, so that the hollow core C easily breaks at the boundary between the hollow core C and the support portion F, allowing the hollow core C to be easily removed. The support portion F has a diameter at the top end face of 2 mm to 15 mm. If the diameter is less than 2 mm, it becomes difficult to support the hollow core C, and the hollow core C may become deformed. On the other hand, if the finished area of the hollow core C after being folded near the boundary between the hollow core C and the support portion F (near the top end face) exceeds 15 mm, not only will the area be too large, making the work difficult, but the finishing work may also cause a loss of dimensional accuracy.
[0066] As described above, the sand layered molding machine 1 of this embodiment can output only low-power laser light, thereby realizing a low cost of the device. Even with low power, the high-ortho-novolac phenolic resin hardens while being heated to about 150°C, and a certain degree of strength is ensured. Therefore, the hollow core C in which the hardened parts that have been irradiated with the laser light and hardened are laminated has at least a strength sufficient to enable it to be removed from the sand layered molding machine 1.
[0067] The hollow core C removed from the sand additive manufacturing machine 1 undergoes secondary firing after finishing at the base of the support part F. In this secondary firing, the hollow core C is heated with particles packed around it. For example, it is heated at 250°C for about six hours in an oven range. The particles packed in during the secondary firing are used to prevent deformation of the hollow core C, i.e., as shape-maintaining members, and the surfaces of which are not covered by oven range, such as glass beads, graphite particles, alumina particles, or silica particles, are used.
[0068] The present invention is not limited to the above-described embodiment, and various modifications can be made within the scope of the claims. For example, when the irradiation of the resin-coated sand layer SL formed (laminated) on the lamination plate 11 with laser light is completed, the lamination plate 11 may rise at a predetermined pitch, and the leveling member 20 may form (laminate) a new resin-coated sand layer SL on the lamination plate 11 after the lamination plate 11 has risen at the predetermined pitch.
[0069] Further, instead of the stacking plate 11 being raised and lowered, the leveling member 20 may be raised and lowered, or the raising and lowering of the stacking plate 11 and the raising and lowering of the leveling member 20 may be combined.
[0070] Furthermore, the leveling member 20 also serves as a supplying means for supplying the resin-coated sand rs stored in the supplying device 30 or the resin-coated sand rs temporarily stored in the flange portion 101 on one end side onto the stacking plate 11, but the supplying device 30 may also supply the resin-coated sand rs onto the stacking plate 11 while moving from one end side to the other end side like the leveling member 20.
[0071] Also, instead of temporarily storing the lump of resin-coated sand rs in the flange portion 101 on one end side, it may be temporarily stored on the stacking plate 11 and then spread out by the leveling member 20 as in this embodiment. EXAMPLES
[0072] Next, the present invention will be described in more detail with reference to examples, but the present invention is not limited to the examples described below. In each example and comparative example, a hollow core having a shape shown in FIG. 6 was molded as a molded object.
[0073] Example 1 The artificial spherical sand used was Cerabeads (registered trademark) #1450 manufactured by Itochu Ceratec Co., Ltd. The particle size distribution was a single peak, with the maximum peak being 0.106 mm.
[0074] The resin used was a fast-curing high-ortho novolac phenolic resin (ortho ratio between 55% and 75%). The ortho ratio was calculated by measuring the absorbance using the KBr method with an infrared spectrophotometer and using the following formula. Ortho rate (%) = D760 ÷ (D760 + 1.44 × D820) × 100 Here, D760 refers to the absorbance at 760 cm-1, and D820 refers to the absorbance at 820 cm-1.
[0075] The descending pitch (layer pitch) was 0.30 mm. The laser output was 25 W, the laser spot diameter was 0.1 mm, the laser scanning speed was 300 mm / sec, and the laser scanning pitch was 0.15 mm. The laser scanning pitch is the distance in the X direction relative to the scanning in the Y direction shown in Fig. 4 and Fig. 5. In Example 1, since the laser spot diameter is 0.1 mm, the laser irradiation areas in adjacent scanning lines in the Y direction do not overlap with each other, and a gap of 0.5 mm is generated.
[0076] If the laser light output is P [W], the laser scanning speed is v [mm / s], the laser scanning pitch is w [mm], and the layer pitch is h [mm], the energy density (E [J / mm]) is calculated as P / (vwh) [ws / mm3] = E [J / mm3], and in the case of Example 1, the energy density is 1.85 J / mm3.
[0077] The bending strength of the core in Example 1 before the second firing was 300 N / cm2.
[0078] Table 1 shows the conditions, energy density, and bending strength.
[0079] [Table 1]
[0080] Table 1 also shows the conditions, energy density, and bending strength for each of the examples and comparative examples from Example 2 onwards.
[0081] Example 2 The same conditions as in Example 1 were used except that the laser output was set to 30 W. The energy density in Example 2 was 2.22 J / mm3. The bending strength of the core in Example 2 before the secondary firing was 639 N / cm2.
[0082] Example 3 The conditions were the same as in Example 1, except that the laser output was 50 W and the laser scanning speed was 500 mm / sec. The energy density in Example 3 was 2.22 J / mm3. The bending strength of the core in Example 3 before the secondary firing was 684 N / cm2.
[0083] Example 4 Except for the laser scanning speed being 750 mm / sec, the same conditions were used as in Example 3. The energy density in Example 4 was 1.48 J / mm3. The bending strength of the core in Example 4 before the secondary firing was 234 N / cm2.
[0084] Example 5 Except for changing the descending pitch (layer pitch) to 0.35 mm, the same conditions were used as in Example 3. The energy density of Example 5 was 1.90 J / mm3. The bending strength of the core in Example 5 before the secondary firing was 720 N / cm2.
[0085] Example 6 Except for changing the layer pitch to 0.40 mm, the same conditions as in Example 3 were used. The energy density of Example 6 was 1.67 J / mm3. The bending strength of the core in Example 6 before the secondary firing was 700 N / cm2.
[0086] Example 7 Except for changing the layer pitch to 0.45 mm, the same conditions were used as in Example 3. The energy density of Example 7 was 1.48 J / mm3. The bending strength of the core in Example 7 before the secondary firing was 733 N / cm2.
[0087] Example 8 Except for changing the layer pitch to 0.50 mm, the same conditions as in Example 3 were used. The energy density of Example 8 was 1.33 J / mm3. The bending strength of the core in Example 8 before the secondary firing was 597 N / cm2.
[0088] Example 9 Except for the laser scanning pitch being 0.16 mm, the same conditions were used as in Example 3. The energy density in Example 9 was 2.08 J / mm. The bending strength of the core in Example 9 before the secondary firing was 642 N / cm.
[0089] Example 10 Except for the laser scanning pitch being 0.17 mm, the same conditions were used as in Example 3. The energy density in Example 10 was 1.96 J / mm. The bending strength of the core in Example 10 before the secondary firing was 728 N / cm.
[0090] Example 11 Except for the laser scanning pitch being 0.18 mm, the same conditions were used as in Example 3. The energy density in Example 11 was 1.85 J / mm. The bending strength of the core in Example 11 before the secondary firing was 609 N / cm.
[0091] Example 12 Except for the laser scanning pitch being 0.19 mm, the same conditions were used as in Example 3. The energy density in Example 12 was 1.75 J / mm. The bending strength of the core in Example 12 before the secondary firing was 600 N / cm.
[0092] (Example 13) Except for the laser scanning pitch being 0.20 mm, the same conditions were used as in Example 3. The energy density in Example 13 was 1.67 J / mm. The bending strength of the core in Example 13 before the secondary firing was 374 N / cm.
[0093] (Comparative Example) The experiment was carried out under the same conditions as in Example 1, except that a random novolac type phenolic resin was used as the resin for coating the surface of the artificial spherical sand. The random novolac type phenolic resin had an ortho ratio of 40% to 50% and a pH of 1 or less.
[0094] In the comparative example, the core (product part) broke when it was removed from the sand additive manufacturing machine. When the bending strength of the broken core fragments was measured, it was only 83 N / cm2.
[0095] In Example 4, the core (product part) was removed from the sand additive manufacturing machine without breaking, but the core was close to breaking. On the other hand, in Example 1, the core (product part) was removed from the sand additive manufacturing machine without any problems. From these results, it is estimated that a bending strength of 250 N / cm2 or more is necessary to ensure that the product part before the secondary firing maintains its shape when it is removed from the sand additive manufacturing machine without losing its shape.
[0096] The cores in each example that were removed from the sand additive manufacturing machine did not have the support parts shown in FIG. 6, and the support parts remained inside the molding frame, buried in the resin-coated sand.
[0097] The cores in each example taken out of the sand additive manufacturing machine were subjected to finishing at the base of the support and then to secondary firing. In the secondary firing, the cores were filled with glass beads and heated in a range oven at 250°C for 6 hours. The broken pieces of the cores in the comparative example were also heated in a range oven at 250°C for 6 hours.
[0098] The bending strength of the core after secondary firing in each Example was 1000N / cm2 or more and 1500N / cm2 or less, which was significantly improved compared to before secondary firing. On the other hand, the bending strength of the broken pieces after secondary firing in the Comparative Example was 1750N / cm2, which was dramatically improved compared to before secondary firing compared to each Example.
[0099] The bending strength of the core after the secondary firing in each example was greater than or equal to the bending strength of a commonly used shell core, and it was confirmed that the core can be used in place of a shell core.
[0100] They also found that a bending strength of 600 N / cm2 is sufficient for the core to function without breaking in actual casting. It could be said that this is over-specified for conventional shell cores, and considering the collapse of the core after casting, a bending strength of 1750 N / cm2 is not necessary. In Examples 2, 3, 5-7, and 9-12, the cores removed from the sand additive manufacturing machine can be used for casting as is without secondary firing.
[0101] Furthermore, it can be seen that in Examples 1 to 13, the energy density is 1.3 J / mm3 or more. Also, when comparing Example 2 and Example 3, the energy density is the same, and both have bending strengths exceeding 600 N / cm2. As for the core molding conditions, the faster the laser scanning speed, the shorter the molding time, so it can be said that Example 3 is more preferable than Example 2. Moreover, the bending strength value of Example 3 is higher than that of Example 2.
[0102] In addition, in terms of the layer pitch, the bending strength far exceeds 600 N / cm2 in Example 3 with a layer pitch of 0.30 mm, Example 5 with a layer pitch of 0.35 mm, Example 6 with a layer pitch of 0.40 mm, and Example 7 with a layer pitch of 0.45 mm, all of which are set to a laser output of 50 W, but in Example 8, in which the layer pitch is expanded to 0.50 mm, the bending strength falls below 600 N / cm2. Since the maximum peak in the particle size distribution of the artificial spherical sand is 0.106 mm, it can be said that the layer pitch, i.e., the thickness of one layer of the resin-coated sand, is 2 to 3 times the maximum peak in Example 3, about 3 times in Example 5, 3 to 4 times in Example 6, about 4 times in Example 7, and 4 to 5 times in Example 8. If the laser output is 50 W, it is preferable that the layer pitch (thickness of one layer of the resin-coated sand) is less than 5 times the maximum peak in the particle size distribution of the sand particles used. If it is more than 5 times, the thermal energy supplied from the laser light is insufficient, the temperature of the resin-coated sand at the bottom of one layer of the resin-coated sand does not rise sufficiently, making it difficult to heat-set, and the bending strength decreases. As a result of investigating the case where the laser output is 25 W, it was found that in this case, the layer pitch (the thickness of one layer of the resin-coated sand) is preferably less than three times the maximum peak in the particle size distribution of the sand particles used. In summary, it is preferable to set the layer pitch to a length greater than 1 time and less than 3 times the particle size of the resin-coated sand. If it is 1 time, the heating efficiency is poor, and the number of layers increases, which lengthens the modeling time. On the other hand, if it is 3 times, the heat of the laser light does not reach the bottom completely, and insufficient hardening or insufficient bonding may become a problem.
[0103] In addition, regarding the laser scanning pitch, the bending strength is 600 N / cm2 or more in Example 9 with a laser scanning pitch of 0.16 mm, Example 10 with a laser scanning pitch of 0.17 mm, Example 11 with a laser scanning pitch of 0.18 mm, and Example 12 with a laser scanning pitch of 0.19 mm, all of which are aligned at a laser output of 50 W. However, in Example 13, in which the laser scanning pitch is expanded to 0.20 mm, the bending strength is significantly below 600 N / cm2. Since the laser spot diameter is 0.1 mm in diameter, a gap of 0.1 mm is generated between the laser irradiation areas in the adjacent Y-direction scanning lines in Example 13, in which the laser scanning pitch is expanded to 0.20 mm. Here, since the maximum peak in the grain size distribution of the artificial spherical sand is 0.106 mm, it is preferable that the interval between the laser irradiation areas in the adjacent scanning lines is approximately equal to or less than the grain size of the sand grain when the laser output is 50 W. In addition, as a result of investigating the case where the laser output is 25 W, it was found that the interval between the laser irradiation areas on adjacent scanning lines is preferably equal to or less than half the grain size of a sand particle. Moreover, whether the laser output is 50 W or 25 W, if the laser irradiation areas on adjacent scanning lines overlap, the thermal energy becomes too large in the overlapping area, so it is preferable that they do not overlap. [Explanation of symbols]
[0104] 1 Sand additive manufacturing machine 10 Modeling frame 11 Laminated Plate 12 Lifting mechanism 20 Leveling materials 30 Feeding device 40 Laser Oscillator 50 Scanner 60 Control section cs artificial spherical sand hof high ortho novolac type phenolic resin rs resin coated sand sp stacking space SL layer B Base plate C hollow core F Support part
Claims
1. A storage area for resin-coated sand, a layer forming means for forming a layer of the resin-coated sand stored in the storage section; an irradiation unit that irradiates the layer with laser light to harden the resin; the layer forming means forms a new layer of resin-coated sand on the layer when the irradiation of the laser light to the layer is completed; The storage unit stores resin-coated sand in which the surfaces of sand particles are coated with a resin having an ortho ratio of 55% or more and 75% or less, The irradiation unit irradiates laser light with an output of 10 W or more and 80 W or less, The output of the laser light irradiated by the irradiation unit is P [W], the scanning speed of the laser light is v [mm / s], the scanning pitch of the laser light is w [mm], the layer pitch in the layer forming means is h [mm], and P / (vwh) [ws / mm] 3 ] = E [J / mm 3 When the energy density E is expressed as: 3 The above described feature of the sand layered molding machine.
2. The irradiation unit irradiates laser light with an output of 10 W or more and 30 W or less, When the output of the laser beam is 10 W or more and 30 W or less, the energy density E of the laser beam is 1.3 J / mm 3 2. The sand layered molding machine according to claim 1,
3. A method for layering sand, comprising alternately repeating a step of forming a layer of resin-coated sand in which the surfaces of sand particles are coated with a resin having an ortho ratio of 55% or more and 75% or less, and a step of irradiating the layer with a laser beam having an output of 10 W or more and 80 W or less to harden the resin, thereby obtaining a hardened layer, and stacking the hardened layers, the method comprising: a first step of forming a base plate by alternately repeating the layer formation and the laser light irradiation; a second step of forming a plurality of support parts, each of which is tapered toward an upper part, at dispersed locations on the base plate by alternately repeating the layer formation and the laser light irradiation; A sand layered manufacturing method, comprising: a third step of alternately repeating the layer formation and the laser light irradiation on the multiple support parts to form product parts connected to each of the multiple support parts.
Citation Information
Patent Citations
Method for producing a layered component
DE19818469A1
Laminating and forming method of sand mold, and manufacture of casting using it
JP1997136139A
Lamination molding method for sand casting mold and production of casting by using the same
JP1997141385A
Powdery particle laminate shaping method and apparatus therefor
JP1998211658A
Lamination shaping method
JP1999005254A